CPR related injuries of the chest wall: direct and indirect fractures - Schenderlein, Anne; Groh, Johannes; Kern, Florian; Perl, Mario; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2025)
BACKGROUND: Rib and sternum fractures are common injuries associated with cardiopulmonary resuscitation (CPR). The fracture mechanism is either direct by application of force on sternum and anterior ribs or indirect by bending through compression of the thorax. The aim of this study was to determine morphologies of rib fractures after CPR and to reevaluate prior findings on fracture localisation, type and degree of dislocation. METHODS: The present study was based on all inpatients treated for chest wall fractures after non traumatic cardiac arrest at a Level 1 Trauma Centre from 2010 to 2016 who had received CT scans. Each fracture was analyzed for location, degree of dislocation and fracture type classified according to AO/OTA and CWIS. We also analysed Fracture Line orientation. RESULTS: We enrolled 40 patients with a total of 423 rib fractures. We found most fractures anterolaterally between the 3rd to 6th rib symmetrically on both sides of the thorax. We found sternum fractures in 30% of the patients, 50% being located at the at the corpus sterni between rib 3 and 4. All patients with sternum fractures suffered from rib fractures and most had fractures of the cartilage or osteochondral junction. All cartilage fractures were straight, undisplaced type A fractures. Most indirect fractures occurred anterolaterally between 50 and 60° in the axial plane. More than 90% of those fractures were classified as type A, 70% showed a straight fracture line and 60% were undisplaced. There was no difference in degree of dislocation between straight and oblique fracture lines. We found 143 incomplete fractures. CONCLUSION: We confirmed prior findings regarding fracture patterns in CPR related injuries. We observed approximately 2-3 times as many straight-lined fractures as oblique ones following indirect trauma. One third of all fractures are incomplete, these highlights the special characteristics like high elasticity of ribs.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Chest wall injury; CPR; Flail chest; Fracture morphology; Indirect fractures; Rib fractures

Traumatic fractures of the sternum – typical distribution and need for subgroups within AO and OTA classification system? - Groh, Johannes; Kern, Florian; Schenderlein, Anne; Krause, Johannes; Perl, Mario; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2025)
Introduction: Objective of this study is the morphologic validation of the AO-classification of the sternal bone and particularly define subgroups. Methods: Analyzed were all patients of a level I trauma center of a 7-year period with fractures of the sternal bone and the anterior rib cartilage. A total number of n = 124 patients was included. The detailed evaluation of the CT-data recorded anatomical basic data of the rib cage and every fracture with its position, dislocation, fracture pattern (which was classified following the AO). Results: 116 (93.5%) patients showed 134 single fractures of the sternal bone, 48 (35.8%) of the manubrium, 81 (60.4%) of the corpus sterni and 5 (3.7%) of the xyphoid. 16 patients had a dual fracture of manubrium and corpus. Fractures of the corpus were mostly type A-fractures, followed by type B-and C-fractures. Manubrial fractures had the same number of type A- and B-fractures. Subgroups were theoretically defined by the senior author of our group and validated. based on location, dislocation and course of the fracture. Discussion: Sternal fractures are mostly shown at the corpus. Fractures of the xiphoid are very uncommon. Generally, corpus fractures are simple fractures, the rarer manubrium fractures show more complex fractures, which presumes a high trauma energy. The defined subgroups can help draw conclusion to the trauma mechanism and its potential concomitant injuries.
CRIS-Team Scopus Importer:2025-07-10
Keywords: AO/OTA classification system; Chest wall injury; Manubrium; Sternal fracture; Sternum fracture